Piezoelectric, elastic, Infrared and Raman behavior of ZnO wurtzite under pressure from periodic DFT calculations - Marana, Naiara Letícia [UNESP]; Casassa, Silvia Maria; Sambrano, Julio Ricardo [UNESP] (Elsevier, 2017)
The influence of pressure on elastic, piezoelectric (total and clamped-ion contribution), dielectric constants, Infrared and Raman spectra, and topological properties of ZnO wurtzite structure was carried out via periodic DFT/B3LYP methodology. The computational simulation indicated that, as the pressure increases, the structure becomes more rigid and an enhancement of the direct piezoelectric response along the z-direction was observed. Bader topological analysis and Hirshfeld-I charges showed a slight increase in the ionic character of Zn–O bond. Besides that, changes in the piezoelectric response are mainly due to the approach between Zn and O than to charge transfer phenomena among the two atoms. Pressure induces a sensitive displacement in the Infrared and Raman frequencies and a decrease of the E2 mode. Nevertheless, the increase of pressure does not lead to a change in the semiconductor character, which proves that the ZnO support high pressures and can be applied in different devices.